Clinical implications of the second and fourth digit ratio in male infertility: associations with semen parameters and sex hormone levels - a cross-sectional study - Gupta, Saurabh; Tripathi, Dhaneshwar; Mathew, Don; Sharma, Mukul; Hasmukhbhai, Korat A.; Sharma, Kalu R.; Verma, Surendra K.; Saiyad, Sajidali S.; Khandelwal, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Oligospermia and hypogonadism are synonymous with infertility in males. Data regarding its correlation with hand digit length and ratio are inconsistent and scarce. The aim was to study the ratio of second (2D) and fourth (4D) fingers of both hands in 236 infertile oligospermic men and their comparison with various clinical and laboratory parameters related to infertility. Methods: In this cross-sectional study, the 2D and 4D length and ratio of both hands of 236 infertile oligospermic men were measured. Semen analysis and hormonal assessment, including serum total testosterone (T), estradiol (E), luteinizing hormone, and follicle-stimulating hormone, were performed and correlated with the 2D: 4D ratio and severity of oligospermia. Participants were further subdivided into two groups according to serum T levels. Results: A significant difference in the 2D: 4D ratio of the right hand was observed between both cohorts and in patients with low T levels. The mean serum T level was significantly lower in infertile oligospermeic males (349.76±115.4 ng/dl; p<0.001) than healthy controls (p<0.001). The testosterone-to-estradiol (T/E) ratio was also significantly lower in the patient group (8.36±4.84; p<0.001). A decline in semen quality, including reduced sperm counts and progressive motility, was observed in patients with low T levels. Conclusion: The 2D: 4D ratio might directly correlate with testosterone levels and, thus, semen quality and fertility potential of a subject. Thus, providing a cost-effective and time-saving method for indirect estimation of androgenization in male patients.